Renal cell carcinoma and amyopathic dermatomyositis - Adili, Anthony F.; Liaconis, Haralambos; Gusenbauer, Kaela; Kapoor, Anil (Canadian Urological Association Journal, 2015)
Amyopathic dermatomyositis (dermatomyositis siné myositis) is a rare disorder with cutaneous lesions identical to those of classic dermatomyositis, but with no clinical evidence of myopathy. Association with malignancy has been suggested in a number of reports. We report the case of a 69-year-old man with a recent diagnosis of amyopathic dermatomyositis, who presented to the urology service with hematuria. Investigations revealed a 5.8- cm renal cell carcinoma and the patient underwent left radical nephrectomy without complication. To our knowledge, an association with renal cell carcinoma and amyopathic dermatomyositis has not been previously described.